Capacity building of integrated health post cadres on stunting prevention in Pandeglang Regency Locus Area - Siti Maulidya Sari; Yusnita Yusnita; Nurul Huda; Kholis Ernawati; Eri Dian Maharsi; Zakiyah Zakiyah; Dini Widianti; Reyhan Muhammad Farras (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Health cadres play a vital role as community educators and frontline workers in the stunting handling program. Maternal knowledge regarding adequate nutrition for toddlers from pregnancy to birth is a crucial factor in preventing stunting, as it influences the mother's choices in terms of food ingredients and diversity. Pandeglang Regency is among the 100 priority cities/regencies in stunting reduction efforts. This activity aims to provide training to enhance the knowledge and capacity of Integrated Health Post (Posyandu) cadres in stunting, anthropometry, and nutrition. The trained cadres will be able to actively contribute to stunting prevention programs in the targeted stunting locus area of the Pandeglang Regency. The training methods include classroom training, Posyandu simulations, advocacy, and licensing. The exercise focuses on three stunting locus villages: Kedeumaneh, Kadeubelang, and Medong. Knowledge improvement was evaluated through pre-test and post-test assessments, followed by simulations conducted at each Posyandu location. The results indicated that 30 cadre respondents demonstrated increased knowledge after the training (p-value = 0.044). Furthermore, the simulation results revealed that the cadres were able to accurately perform anthropometric measurements.